PERANCANGAN APLIKASI MICROSOFT EXCEL PPH21 UNTUK MENGHUBUNGKAN SISTEM INFORMASI PENGAJIAN DENGAN APLIKASI E-SPT PPH21-26 DIREKTORAT JENDERAL PAJAK - Safri, Safri (Universitas Dirgantara Marsekal Suryadarma, 2022)
Regulation of the Direktorat Jenderal Pajak Nomor PER - 14/PJ/2013 dated April 18, 2013 starting in 2014 which is still valid until now, where in the implementation of taxation PPh21-26 uses e-SPT as a means of reporting PPh 21/26. The purpose of the e-SPT PPh21-26 is to make it easier for companies to carry out their PPh21-26 obligations. The application application is connected to the company's recitation information system, and of course a bridge is needed to be able to connect the two applications, the tax application and the recitation application. This study aims to create an application that can quickly, precisely, effectively, and efficiently manage salary data in the company, so that it is able to meet the elements of taxation, especially PPh21 period and annual PPh21/proof of deductions that must be submitted to employees at the beginning of time, in order to avoid burdens piling up. or queues for the submission or reporting of individual annual PPh21. The application is designed using Microsoft Excel, forms it using excel formulas, connects it with sheet per sheet, so as to be able to produce what is desired in this study, the simulated data is tried to be imported into the e-SPT PPh21-26 system with the result that there are no problems. , and also very easy to use, saves processing time, improves tax accuracy and makes it easier for companies to reportÂ Keywords: e-SPT PPh21-26, Microsoft Excel